THE EFFECT OF CASH FLOW COMPONENTS AND FIRM SIZE ON STOCK RETUNS IN BANKING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Sari, Bella Mega (Jurnal KIAFE, 2022)
This research aims to determine the effect of cash flow statement components and firm size partially and simultaneously on stock returns in banking sector companies listed on the Indonesia Stock Exchange. The independent variables used in this research are Operating Activity Cash Flow (CFO), Investing Activity Cash Flow (CFI), Financing Activity Cash Flow (CFF), and Firm Size as measured by the company's total assets. While the dependent variable used in this research is Stock Return. The research method used is quantitative associative. The number of research samples is 37 banking sector companies listed on the Indonesian stock exchange for 2017, which are determined based on the purposive sampling method so that the research data derived from financial statements are 37 data. The analysis technique used is multiple linear regression analysis. The results showed that partially, financing activity cash flow has a positive and significant effect on stock returns, whereas operating activity cash flow, investment activity cash flow, and firm size does not affect stock returns. Simultaneously, all components of the cash flow statement consisting of operating activity cash flow, investing activity cash flow, and financing activity cash flow, as well as firm size do not affect stock returns.